EFEKTIVITAS PENGGUNAAN APLIKASI ONLINE FOOD DELIVERY UNTUK MENINGKATKAN PENJUALAN: (Studi Kasus pada Pelaku UMKM Seblak di Kota Tasikmalaya) - Janati Piddiani; Innayati Aprilia; Lilis Karlina (Transpublika Publisher, 2022)
Online transportation has been able to help UMKM actors in distributing and promoting their products, namely through online food delivery services consisting of GoFood, GrabFood, ShopeeFood and Maxim Food & Goods applications. This study aims to determine the effectiveness of using online food delivery services in increasing sales of Seblak SME’s in Tasikmalaya City. The research method used in this study is a qualitative research method with a case study design. The sampling technique used was purposive sampling technique. To prove the effectiveness of the use of online food delivery services in increasing sales, 6 business actors who are Seblak SME’s and use the online food delivery services for a minimum of one month are set to prove the effectiveness of using online food delivery services. The data collection was done by observation and interviews. Based on the information obtained, the use of this online food delivery services is effective in increasing sales of Seblak SME’s in the City of Tasikmalaya by assessing several aspects such as productivity, ability to earn profit, ability to adapt and job satisfaction.